EFEKTIVITAS HEARING CONSERVATION PROGRAM TERHADAP PENCEGAHAN PENINGKATAN AMBANG DENGAR DI INDUSTRI MANUFAKTUR - Ida Rahmawati; Yuliani Setyaningsih; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Increased hearing threshold is acute or chronic hearing loss caused by noise exposure that it can reduce the ability of auditory sense function. The hearing threshold in people can be detected by doing an audiometric test to determine hearing ability in certain intensity. Based on preliminary studies, one manufacturing industry in Semarang, Central Java has implemented the Hearing Conservation Program, one of the efforts to control the potential noise hazards. The aim was determine the relationship between the effectiveness of the Hearing Conservation Program implementation with an increased hearing threshold for workers. The research design was descriptive analytic with cross sectional approach. The sampling technique used a total sampling of 26 respondents who were workers in the work area with noise>85 dBA, and had done audiometry tests. The research instruments used were questionnaires and observation sheets from the National Institute for Occupational Safety and Health (NIOSH) in A Practical Guide to Effective Hearing Conservation Programs in the Workplace with publication number 90-120 Appendix A, namely OSHA Noise Standard Compliance Checklist. Statistical analysis using the Rank Spearman. The results was no relationship age (p-value 0.607), and work period (p-value 0.162), and disease history (p-value 0.282) increase threshold in manufacturing industry workers. The application of the Hearing Conservation Program in the manufacturing industry in this case includes an effective one with a work <5% that is equal to 0.38%. Researchers to conduct safety briefings on workers who are in a very high work area and provide benefits for personal protective equipment while working.